Self-issuing jets for suppression of vortex-induced vibration of a single box girder. (April 2019) - Chen, Wen-Li; Yang, Wen-Han; Li, Hui
Abstract: The control of vortex-induced vibration (VIV) is very important for the safety of a bridge during its service life. In the present study, a self-issuing jet, which is a type of a passive control method, is installed on a bridge deck to suppress the VIV and to validate the control effect. This study focuses on the layout of the slits in a deck test model and compares the near-wake flow fields between the baseline and optimal-control cases. The experimental results show that the self-issuing jet plays an important role in controlling the vibration. The vertical VIV (V-VIV) is fully suppressed, and the maximum amplitude of the torsional VIV (T-VIV) is reduced by 45.5%. The Strouhal number ( St = fB / U, where f and B are the frequency and reference length of the structure, respectively, and U is the incoming speed) of the best control case (Case II) in which the self-issuing jets are arranged at the upper half part of the lower inclined panel in the box section increases compared with that in the baseline case. The wake-flow structures in the V-VIV and T-VIV are also studied. The results show that the wake patterns are modified by the self-issuing jet. In the V-VIV case, the alternating wake-flow structures are changed into a relatively steady state and show a slight variation with time in the control case, i.e. Case II. In the T-VIV case, the strength of the spanwise vortex is reduced, whereas the streamwise vortex is increased by the self-issuing jet. Moreover, a Mode-B flow pattern is found in the wake flow field of the test model in Case II, which implies that the secondary wake instability is triggered by the self-issuing jet.